2022
DOI: 10.1007/s12207-022-09448-y
|View full text |Cite
|
Sign up to set email alerts
|

Scores in Self-Report Questionnaires Assessing Adult ADHD Can Be Influenced by Negative Response Bias but Are Unrelated to Performance on Executive Function and Attention Tests

Abstract: Self-report questionnaires are in widespread use in the assessment of adults with suspected attention-deficit and hyperactivity disorder (ADHD). Notwithstanding the high degree of validity, these questionnaires are considered to possess, their stand-alone use in assessment for adult ADHD may result in false-positive diagnoses due to the risk of negative response bias. Most of the self-report questionnaires in typical use are based on the diagnostic systems DSM-5 or ICD-10. From a neuropsychological point of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Moreover, the SRSI failure rate of 10%–18.2% in psychotherapy clients is consistent with the estimated base rate of 15% for symptom overreporting across all clinical neuropsychological evaluations (Martin & Schroeder, 2020). Using the SIMS, Dandachi-FitzGerald et al (2016) and Bodenburg et al (2022) observed similar rates of symptom validity test failure in clinical patients: 14.1% and 17.6%, respectively. These findings indicate that symptom overreporting occurs in clinical (nonforensic) assessments.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the SRSI failure rate of 10%–18.2% in psychotherapy clients is consistent with the estimated base rate of 15% for symptom overreporting across all clinical neuropsychological evaluations (Martin & Schroeder, 2020). Using the SIMS, Dandachi-FitzGerald et al (2016) and Bodenburg et al (2022) observed similar rates of symptom validity test failure in clinical patients: 14.1% and 17.6%, respectively. These findings indicate that symptom overreporting occurs in clinical (nonforensic) assessments.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the degree of hyperactivity and inattention was assessed using the two subscales of the SWAN which were part of the test booklet sent to twins and answered by themselves (not their parents or teachers). Although the items were derived from the DSM-IV-TR (American Psychiatric Association 2008 ), research suggests that one needs a more robust assessment (for example a clinical interview and/or neuropsychological assessment) for a more reliable distinction between subjects with and without ADHD (see e.g., Bodenburg et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast to this outdated practice, experts now seem to agree that patient groups cannot be unequivocally considered “bona fide comparison groups” for experimental simulation studies because invalid test results can and do occur outside of the medicolegal/forensic context. For example, in one of the studies included in this special issue, the percentage of SVT failure was as high as 18.1% in a group of individuals assessed prior to psychotherapeutic treatment (Dandachi-FitzGerald et al, 2023), and previous studies have observed similar failure rates in other clinical samples with different SVTs (Bodenburg et al, 2022; Dandachi-FitzGerald et al, 2016; Schroeder & Martin, 2022). Of note, certain SVTs sometimes seem to yield a relatively high number of positive results even in nonclinical contexts (Boskovic et al, 2022; Zahid et al, 2023).…”
mentioning
confidence: 93%